Changes in Empathy Mediate the Effects of Cognitive-Behavioral Group Therapy but Not Mindfulness-Based Stress Reduction for Social Anxiety Disorder. Issue 6 (November 2019) - Morrison, Amanda S.; Mateen, Maria A.; Brozovich, Faith A.; Zaki, Jamil; Goldin, Philippe R.; Heimberg, Richard G.; Gross, James J.
Abstract: Social anxiety disorder (SAD) has been shown to be associated with difficulty in the ability to vicariously share others' positive emotions (positive affective empathy). Mixed evidence also suggests potentially impaired recognition of the positive and negative emotions of others (cognitive empathy) and impaired or enhanced sharing of the negative emotions of others (negative affective empathy). Therefore, we examined whether two efficacious treatments for SAD, cognitive-behavioral group therapy (CBGT) and mindfulness-based stress reduction (MBSR), improve empathy in SAD relative to a wait-list condition and whether improvements in empathy mediate improvements in social anxiety. In the context of a randomized controlled trial, participants with SAD completed an empathy task at baseline, posttreatment/wait-list ( N = 81), and 1-year follow-up ( N = 37). Relative to both MBSR and wait-list, CBGT resulted in significant improvements in positive affective empathy. CBGT-related changes in positive affective empathy also mediated improvements in social anxiety at both posttreatment/wait-list and at 1-year follow-up. Other indices of empathy did not change differentially across the three conditions. Therefore, one way in which CBGT may specifically confer benefits to individuals with SAD is through increasing their ability or willingness to share in the positive emotions of others. Highlights: Empathy was examined as a mechanism of treatment for social anxiety disorder. Cognitive-behavioral group therapy (CBGT) improved the sharing of positive emotions. Improved sharing of positive emotions also mediated improvement in CBGT. Mindfulness-based stress reduction (MBSR) did not improve empathy.